2000
DOI: 10.1086/309527
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Coronal Magnetic Loops

Abstract: Observed coronal loops have a surprisingly uniform thickness that cannot be easily understood in terms of standard coronal magnetic Ðeld models. We investigate the possibility that the uniform thickness can be explained by locally enhanced twist in the Ðeld, so that observed loops correspond to twisted coronal Ñux tubes. Our approach is to construct numerical models of fully three-dimensional force-free magnetic Ðelds. To resolve the internal structure of an individual loop embedded within a much larger dipole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…Dymova & Ruderman (2005) showed that kink oscillations of thin magnetic tubes with the density varying along the tube can be described by the wave equation with the phase speed equal to the local kink speed. Although typically the coronal loop expansion is relatively small, the ratio of the loop cross-section radii at the apex and at the footpoints can still reach a value of 1.5 Klimchuk et al 2000). It is surprising that in the chromosphere the expansion of vertical magnetic flux tubes can reach a value of up to a few hundred (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Dymova & Ruderman (2005) showed that kink oscillations of thin magnetic tubes with the density varying along the tube can be described by the wave equation with the phase speed equal to the local kink speed. Although typically the coronal loop expansion is relatively small, the ratio of the loop cross-section radii at the apex and at the footpoints can still reach a value of 1.5 Klimchuk et al 2000). It is surprising that in the chromosphere the expansion of vertical magnetic flux tubes can reach a value of up to a few hundred (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This represents a natural stressing mechanism of the magnetic field that eventually leads to a relaxation and a release of magnetic energy (e.g., Golub et al 1980;Klimchuk et al 2000;López Fuentes et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…For curved flux tube models previous work has addressed how the current sheets formed (e.g. Török et al 2004), how the loops responded to twist being injected through foot points (Van Hoven et al 1995;Amari et al 1996;Amari & Luciani 1999;Klimchuk et al 2000;Török & Kliem 2003;Tokman & Bellan 2002;Gerrard et al 2004;Aulanier et al 2005) and how kink unstable loops erupt through overlaying arcades (e.g. Török & Kliem 2005;Fan 2005).…”
Section: Introductionmentioning
confidence: 99%